Effects of Dried and Fermented Quail Waste-Based Concentrate Substitution on Slaughter Weight and Carcass Characteristics of Joper Chickens - Tri Ida Wahyu Kustyorini; Enike Dwi Kusumawati; Muhammad Danial Ulum (Jurnal Ilmu Dan Teknologi Peternakan Indonesia (JITPI) Indonesian Journal of Animal Science and Technology), 2026)
Feed constitutes the largest cost component in poultry production; therefore, alternative feed ingredients that are economical and sustainable are required. This study aimed to analyze the effect of concentrate substitution using Dried and Fermented Quail Waste (DFQW) on slaughter weight and carcass percentage of Joper chickens. The experiment was conducted using a Completely Randomized Design with four treatments and three replications, namely P0 (100% concentrate), P1 (95% concentrate + 5% DFQW), P2 (90% concentrate + 10% DFQW), and P3 (85% concentrate + 15% DFQW). A total of twelve male Joper chickens aged four weeks were used and reared until the end of the experimental period. The observed variables included slaughter weight and carcass percentage. Data were analyzed using analysis of variance (ANOVA) followed by the Least Significant Difference (LSD) test. The results showed that DFQW substitution had a highly significant effect (P < 0.01) on slaughter weight and carcass percentage of Joper chickens. Treatment P1 produced a slaughter weight (865.67 g) comparable to the control (891.33 g) and the highest carcass percentage (58.67%). In contrast, increasing DFQW levels to 10% and 15% resulted in decreased slaughter weight and carcass percentage. It can be concluded that DFQW can be used as a concentrate substitute up to a level of 5% without reducing the production performance of Joper chickens.